加快推进中国河北省经济国际化的思考 = On accelerating economic internationalization of Hebei provincial economy - 才利民 Cai, Limin (2009)
The subject dissertation specifically analyses the favorable and unfavorable conditions and relative measures for accelerating Hebei's economic globalization process in the framework of the international trade theory by combining positive and normative analysis.